Work-life balance of librarians at the Kenneth Dike Library in Nigeria: implications for the provision of library services (2020)
Purpose – This study examined the interceding influence of work–life balance (WLB) among library staff at the Kenneth Dike Library and its implication for the provision of information. The research sought to respond to the following questions: the effect of demographic variables on the WLB of librarians and their perceptions of WLB within the intimate environment. Design/methodology/approach – This study adopted a positivist research paradigm because the nature of the research revealed a single social reality which can be measured quantitatively, using a reliable instrument such as a questionnaire. The total sampling technique was used to zero in on the staff of the library, in which the entire library population was included in the study. Findings – The findings suggest that male librarians enjoy a better WLB than their female counterparts. Also, the results indicate that librarians, irrespective of their marital status, focused on job-related activities minding their marital status and therefore, marital status could influence the WLB of librarians. Similarly, priority is not being given to their work, to the detriment of caring for the family. Research limitations/implications – The study suggests that age causes the WLB to change, the implication being that an ageing workforce has an impact on adaptation, output and innovation. Originality/value – This paper sheds light on the WLB among librarians at the Kenneth Dike Library (KDL); therefore, information acquired from this study is imaginative and valuable to understand better how information professionals react to official and personal engagement.